Non-destructive testing of tennis strings - Phuong, Luong Minh (Vietnam Journal of Mechanics, 2008)
The paper aims to illustrate three advantages of infrared thermography as a non-destructive, non-contact and in real time technique (a) to detect the occurrence of intrinsic dissipation localisation, (b) to observe the progressive damage processes and mechanisms of gut failure, and to determine the optimal tensions for each type of tennis strings. Experimental results evidence a limit of acceptable damage beyond which string will fail due to coalescence of defects and/or weakness zones.